ANALISIS PENGGUNAAN KONTRASEPSI SUNTIK TERHADAP GANGGUAN MENSTRUASI - Siti Qomariah (Jurnal Asuhan Ibu dan Anak, 2018)
Maternal and Child Health Problems (MCH) is still a health problem in Indonesia. This is because the high maternal mortality rate (MMR). To tackle the government's 2-KB program is better by promoting contraceptive use. Injectable contraception is one of the most popular methods of counter-effects. One of the disadvantages of counter-injection is the disruption of menstrual patterns such as amenorrhea, spotting occurs. The purpose of this study was to determine the analysis of contraceptive use of injections against menstrual disorders in Sail Work Area Sail 2016. The approach taken is a quantitative analytical observational approach with crossectional research design to know the Analysis of contraceptive use of injection against menstrual disorders. The research instrument used is questionnaire. The population in this study used women of childbearing age who use contraception injecting as much as 83 respondents with Consecutive Sampling. Data analysis is univariate and bivariate analysis. The result of this research is 1 month injection acceptor for as many as 39.8% (33 people), 3 months injecting 3-month injection acceptor as much as 60.2% (50 people) and there is relationship between contraceptive use to menstrual disorder with P value 0.003 < = 0.05) . From this study the use of injecting contraception either 1 month injection or 3 month injection associated with the occurrence of menstrual disorders. This is related to the addition of hormones obtained from the use of injectable contraceptives that cause hormone imbalance in the body.afrom (